FRI0633-HPR "It Might Hurt, but Still It's Good": People with Rheumatoid Arthritis Beliefs and Expectations about Physical Activity Interventions. (15th July 2016) - Larkin, L.; Kennedy, N.; Fraser, A.; Gallagher, S.
Abstract : Background: People who have Rheumatoid Arthritis (RA) report low levels of physical activity despite the many health benefits of being physically active [1, 2]. Involving key stakeholders is important when designing interventions which target behaviour change as it allows consideration of particular issues that may influence the delivery of complex interventions [3, 4]. Objectives: This study aimed to explore the views of people who have RA on being physically active and the design of a future physical activity intervention. Methods: A qualitative methodology using a constructivist approach was employed. Recruitment was through an outpatient rheumatology clinic in an urban hospital. Interviews were conducted by telephone, with an interview question guide being used by the interviewer. Interviews were transcribed and analysed using thematic analysis. Transcripts were read, notes made and ideas formulated to facilitate coding. The research team searched for patterns, analysed and coded the data, and generated sub-themes and themes. Themes were reviewed by the research team to check if the themes worked in relation to the coded extracts and the entire data set. Results: Twelve females and five males participated in the study. Their mean age was 59.8 years (range 35–83, SD 12.5) and mean disease duration was 13.7 years (range 1–47, SD 15.3). Four main themes were generated: " Being active ", " Barriers and facilitators ", " Information and advice ", and " Supporting physical activity ". " Being active " encapsulated the participants' understanding of physical activity, their perceptions' that they could be active and their physical activity limits due to having RA. Beliefs and emotions were highlighted as both key barriers and facilitators to being active, e.g. fear about increasing disease activity by "overdoing it" whilst locating an intervention in a hospital setting was discussed as being negative. The need for accurate information about being physically active from a credible source was highlighted in " Information and advice ", whilst goal setting, monitoring and social support were thought to be important to support physical activity. Conclusions: There is a lack of information and knowledge about being physically active amongst people who have RA, which contributes to uncertainty about being active. Future interventions should consider delivery in a group, community setting and should incorporate methods which support and monitor behaviour. This study highlights the importance of involving key stakeholders when designing future physical activity interventions as such contributions can help to ensure that such interventions are successful. References: Sokka et al (2008) Physical inactivity in patients with rheumatoid arthritis: data from twenty-one countries in a cross-sectional, international study. Arthritis Rheum (Arthritis Care & Res) 59(1):42–50 Cooney et al (2011) Benefits of exercise in rheumatoid arthritis. Journal of Aging Research Article ID 681640 Medical Research Council (2008) Developing and evaluating complex interventions: new guidance. http://www.mrc.ac.uk/Utilities/Documentrecord/index.htm?d=MRC004871 /p> National Institute for Health and Clinical Excellence (2007) Behaviour Change at Population, Community and Individual Levels. NICE Public Health Guidance. London: NICE Disclosure of Interest: None declared